2006
DOI: 10.1002/eji.200636400
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of GATA3 in Protein Kinase C θ‐induced Th2 cytokine expression

Abstract: Protein kinase C theta (PKCtheta) is essential for T cell activation, as it is required for the activation of NF-kappaB and expression of IL-2. PKCtheta has also been shown to affect NFAT activation and Th2 differentiation. To better understand the role of PKCtheta in the regulation of T helper cells, we used PKCtheta-deficient DO11.10 transgenic T cells to study its role in vitro. DO11.10 Th1 cells deficient in PKCtheta produced significantly less TNF-alpha and IL-2. The expression of Th2 cytokines, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…These data extend previous in vitro observations for anti-CD3/CD28-stimulated CD4 T cells, which also revealed that PKC-is involved in the upregulation of GATA3 (43). In addition, Th2 differentiation of Leishmania and Nippostrongylus brasiliensis-specific CD4 T cells is PKC-dependent (27).…”
Section: Discussionsupporting
confidence: 89%
“…These data extend previous in vitro observations for anti-CD3/CD28-stimulated CD4 T cells, which also revealed that PKC-is involved in the upregulation of GATA3 (43). In addition, Th2 differentiation of Leishmania and Nippostrongylus brasiliensis-specific CD4 T cells is PKC-dependent (27).…”
Section: Discussionsupporting
confidence: 89%
“…49). Moreover, PKC promotes Th2 cytokine expression (47,50). It is conceivable that IRE1␣ contributes to the TCR-induced PKC activation of IL-4.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, protein kinase C (PKC) u appears to regulate NF-kB activation and GATA3 expression. In PKCu-deficient CD4 T cells, the expression of GATA3 was severely impaired and Th2 cytokine production decreased [27]. Moreover, PKCu was reported to be a downstream target of Notch3 [28].…”
Section: Regulation Of Gata3 Expressionmentioning
confidence: 98%